IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH DI DESA PUTAT NUTUG, KECAMATAN CISEENG, KABUPATEN BOGOR - Rahma Eka Anggraeni (2022)
Policies are made to completely solve problems that arise in the community such as waste problems, but in practice there are still many people in the waste management process carried out by improper disposal, causing waste generation as happened in Putat Nutug Village, Ciseeng District, Bogor Regency which refers to in Bogor Regency Regional Regulation 2 of 2014 concerning waste management. The purpose of this study is to find out how to optimize the implementation of waste management policies in Putat Nutug Village so that it can run optimally and to find out efforts to overcome waste problems that occur in Putat Nutug Village. The research method used is qualitative research. The research technique was carried out by means of observation, in-depth interviews and documentation studies. The participants used in this study were representatives from the Bogor Regency Environmental Service, the Village secretary, the Walagri Waste Bank Coordination, Walagri Waste Bank customers, and non-customers of the Walagri Waste Bank. The results of the study stated that waste management in the village was still not good this was due to the absence of land for the construction of temporary shelters, facilities and infrastructure that were still not good, and the level of public awareness was still low on the importance of waste management. Suggestions that can be given are to disseminate information about good and correct waste management and allocate village funds for waste management in the village. Keywords: Waste Problems, Community Participation, Implementation of Bogor Regency Regional Regulation 2 of 2014 concerning waste management